Personality, Social Identity, and Individual Differences in Multinational Decision-Making. (September 2017) - Matthews, Gerald; Reinerman-Jones, Lauren; Burke, Shawn; Teo, Grace; Scribner, David
Contemporary military operations require the US to partner with coalition nations, so that commanders must make effective decisions for multinational teams. The effectiveness of decision-making may depend on various factors. General decision-making competence and personality traits that promote interpersonal functioning may be advantageous in the team context. Sociocultural factors such as a strong nationalistic social identity may be harmful to decision-making in multinational teams. The current study ( N =696) examined correlates of a Situation Judgment Test (SJT) for multicultural decision-making ability in multiple samples. Predictors of better SJT performance included general decision-making ability, low nationalism, and various personality traits. Multivariate analyses discriminated multiple, independent predictors. Findings suggest assessment of the various strengths and weaknesses that shape the individual's decision-making may inform training for multicultural competence.